(untitled) (Journal of the College of Basic Education, 2026)
This study investigates the effectiveness of the (V) diagram strategy as a structured framework for planning and implementing teaching strategies. By defining key elements, classifying activities, and setting learning objectives, the model contributes to enhancing students’ conceptual understanding and achieving learning goals more efficiently.The researcher ensured the equivalence of the experimental and control groups statistically before starting the experiment, based on several variables (prior knowledge test, mid-year history grades for the academic year 2023/2024, and Raven’s IQ test). Instructional plans and behavioral objectives were developed and reviewed by a panel of experts for validation and modification. A research instrument (a historical concept acquisition scale) was constructed, and item difficulty and discrimination indices were calculated. The null hypothesis was rejected due to statistically significant differences in favor of the experimental group. This superiority is attributed to several factors: The (V) diagram represented a novel approach for students, which increased their motivation toward the subject.The use of the (V) model contributed to improved comprehension and understanding of the subject matter. It encouraged autonomous learning, allowing students to construct knowledge independently, unlike traditional methods where the teacher is the sole source of information and students are passive recipients. Conclusions: The (V) diagram model positively influenced students’ commitment to completing assignments and attending classes regularly. It positioned students at the center of the educational process, reducing reliance on the teacher as the primary source of knowledge. Recommendations and Suggestions: Provide teachers with booklets and resources on modern teaching strategies and models for implementation in classrooms. Conduct further research on the impact of the (V) diagram model on students’ academic achievement in history.